Health state utility values and associated complication-related difference in community-based adults with type 2 diabetes in Nanjing China: a cross-sectional study - Huang, Qiaoyu; Xie, Hui; Wang, Zhiyong; Fan, Zhuanzhuan; Sun, Simeng; Zhang, Ting; Yang, Huafeng; Shen, Ya (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to derive health state utility values (HSUVs) in community-based adults with type 2 diabetes from Nanjing, China, and to examine the differences associated with diabetes-related complications.MethodsA cross-sectional study employing a multi-stage random sampling method was conducted in Nanjing, China, in 2024. A total of 2,153 participants were finally included in the analysis. The Chinese version of EQ-5D-3L was used to assess health states, and the corresponding China value set was applied to convert these health states into HSUVs. Participants’ demographic characteristics and complication profiles were collected via a standardized questionnaire. Unadjusted and adjusted HSUV estimates were generated using multiple linear regression models with robust standard errors.ResultsIn the sample, 73.39% reported no problem in all five dimensions of the EQ-5D-3L, and none reported severe problems in any dimension. The mean overall HSUV was 0.9672. The unadjusted analyses showed that participants with any complication had lower HSUVs than those without any complication (all p-values < 0.001). In the fully adjusted model, participants with eye-related, cardiovascular, cerebrovascular and other complications (e.g., mental and oral diseases) were associated with decrements in HSUVs (all p-values < 0.05). Additionally, marital status and employment were identified as significant predictors of HSUVs (all p-values < 0.05).ConclusionOur study suggests that health utility is not significantly impacted in community-based adults with type 2 diabetes in Nanjing, China. However, people with eye-related, cardiovascular and cerebrovascular complications may require additional attention and care to mitigate decrements in health utility.